Fast atom interaction with surfaces at grazing incidence: classical and quantum scattering applied to thin film growth. Issue 20 (January 2020) - Staicu Casagrande, E M; Momeni, A; Khemliche, H
Synopsis: Characterization of solid surfaces with heavy particles has mainly relied on the use of ions at energies from keV to MeV. Although atomic diffraction at thermal energies has been known since 1930 and became popular in the 1970's as a powerful surface characterization technique, it is nowadays rather confidential. Unexpectedly, diffraction with atoms in the keV range has also been observed despite the tininess of the de Broglie wavelength. Grazing Incidence Fast Atom Diffraction (GIF AD) has now become mature and allows the real-time analysis, during the growth, of the most fragile layers.